EZH2 inhibition reactivates epigenetically silenced FMR1 and normalizes molecular and electrophysiological abnormalities in fragile X syndrome neurons - Fang, Minggang; Deibler, Sara K.; Krishnamurthy, Pranathi Meda; Wang, Feng; Rodriguez, Paola; Banday, Shahid; Virbasius, Ching-Man; Sena-Esteves, Miguel; Watts, Jonathan K.; Green, Michael R. (Frontiers in Neuroscience, 2024)
Fragile X Syndrome (FXS) is a neurological disorder caused by epigenetic silencing of the FMR1 gene. Reactivation of FMR1 is a potential therapeutic approach for FXS that would correct the root cause of the disease. Here, using a candidate-based shRNA screen, we identify nine epigenetic repressors that promote silencing of FMR1 in FXS cells (called FMR1 Silencing Factors, or FMR1-SFs). Inhibition of FMR1-SFs with shRNAs or small molecules reactivates FMR1 in cultured undifferentiated induced pluripotent stem cells, neural progenitor cells (NPCs) and post-mitotic neurons derived from FXS patients. One of the FMR1-SFs is the histone methyltransferase EZH2, for which an FDA-approved small molecule inhibitor, EPZ6438 (also known as tazemetostat), is available. We show that EPZ6438 substantially corrects the characteristic molecular and electrophysiological abnormalities of cultured FXS neurons. Unfortunately, EZH2 inhibitors do not efficiently cross the blood-brain barrier, limiting their therapeutic use for FXS. Recently, antisense oligonucleotide (ASO)-based approaches have been developed as effective treatment options for certain central nervous system disorders. We therefore derived efficacious ASOs targeting EZH2 and demonstrate that they reactivate FMR1 expression and correct molecular and electrophysiological abnormalities in cultured FXS neurons, and reactivate FMR1 expression in human FXS NPCs engrafted within the brains of mice. Collectively, our results establish EZH2 inhibition in general, and EZH2 ASOs in particular, as a therapeutic approach for FXS.